Pelatihan Packaging Kripik Ubi Madu Dengan Metode Vacuum Sealer Pada Kelompok Dasa Wisma Brayat Ageng Nyai Roso Putih Dusun Nglurah Kelurahan Tawangmangu Jawa Tengah - Elmira Elmira; Bias Nur; Sintaria Praptinasari; Rahayu Mekar Bisono; Fredy Susanto; Imam Basuki (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2023)
In the vicinity of Nglurah Hamlet, there are tubers that are abundant with sweet potatoes which are usually used by the local residents for food. However, in Nglurah Hamlet, honey potatoes have not been maximized. Empowerment for community development since the pandemic was directed at realizing quality training activities both in terms of hard and soft skills. By providing training solutions to the residents of Nglurah Hamlet in the form of life skills, in the form of training on packaging honey sweet potato chips with the vacuum sealer method for the Dasa Wisma group in the plantation sector to be applied in everyday life, both in the world of work and entrepreneurship, and ready to compete in competition. in the world of work. The implementation of activities is given using a training method with a model of delivery of material theory of packaging processes, practice of using sealers and packaging to facilitate sales. This certainly made a real contribution related to increasing the economic value of products in Nglurah Hamlet, this activity was welcomed and carried out properly according to plan.